Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1515/hmbci-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Omicron variant in COVID-19 current pandemic: a reason for apprehension

Abstract: COVID-19 emerged in Wuhan, China, but was caused by the original coronavirus, severe acute respiratory syndrome associated coronavirus-2 (SARS-CoV2). In early 2020, there was a widespread breakout of cases well over world, resulting in an epidemic that rapidly escalated to become a pandemic. This abruptly shook the global healthcare system. The emergence of the alpha, beta, and delta SARS-CoV-2 were associated with new waves of infections, sometimes across the entire world but until this month i.e., between No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…In Italy, in the last week of January 2023 from 27 January to 2 February 2023, 33,042 new cases were reported by the National Health Authorities along with 439 deaths [2]. New variants of interest and concern have emerged and spread [3], such as the Omicron variant and its sublineages [4]. Massive vaccination campaigns have reduced the burden of the virus on healthcare systems worldwide, consistently protecting people against severe forms of illness [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, in the last week of January 2023 from 27 January to 2 February 2023, 33,042 new cases were reported by the National Health Authorities along with 439 deaths [2]. New variants of interest and concern have emerged and spread [3], such as the Omicron variant and its sublineages [4]. Massive vaccination campaigns have reduced the burden of the virus on healthcare systems worldwide, consistently protecting people against severe forms of illness [5].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study conducted by Vandana S. Daulatabad et al , also observed that lack of physical activity and excessive smartphone had a negative impact on physical and mental health. [ 36 37 ] A study conducted by Anne-Linda Camerini et al ,[ 38 ] also found out that increased screen time was a risk factor for mental health problems. Recent studies show that excessive use of screens, including computer screens and smartphones, is associated with serious mental problems and cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable mutations are N501Y, D614G, and E484K, which allow the virus to escape the protection offered by currently available vaccines. These structural changes also distort the antibody binding sites, further compromising the immune response to the infection (Kamble et al, 2022).…”
Section: Variants Of Coronavirusmentioning
confidence: 99%